Pengembangan Aplikasi Rental Mobil Berbasis Web Menggunakan Model Agile di CV. Endang Jaya - Humaedi, Dedi; Ferizal, Ferizal; Putra, Alvin Pratama; Saifudin, Aries; Yulianti, Yulianti (Jurnal Informatika Universitas Pamulang, 2021)
In the current era of globalization, car or motorcycle rental service providers are now widely found in various parts of the city and the role of the internet is very important to convey accurate and efficient information, CV Endang Jaya is a car rental service provider located in Tangerang Regency. In delivering information, CV Endang Jaya has used a web-based information system that provides information about car rental prices and types of cars for rent, of course the system requires the development of a computerized system, for example in the transaction process, the availability of cars because customers are often disappointed with the unavailability of the car to be purchased. for rent because there is no available information system, the Software Development Method used is Agile. With the development of this web-based car rental application, it is hoped that the company owner can solve the problems that are currently happening. So that it can make it easier to find out the availability of the car.